2018
DOI: 10.3390/v10060331
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas PB1-Like Phages: Whole Genomes from Metagenomes Offer Insight into an Abundant Group of Bacteriophages

Abstract: Despite the abundance, ubiquity and impact of environmental viruses, their inherent genomic plasticity and extreme diversity pose significant challenges for the examination of bacteriophages on Earth. Viral metagenomic studies have offered insight into broader aspects of phage ecology and repeatedly uncover genes to which we are currently unable to assign function. A combined effort of phage isolation and metagenomic survey of Chicago’s nearshore waters of Lake Michigan revealed the presence of Pbunaviruses, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…It can cause diseases in plant and animal species, as well as in humans [ 481 ], which has recently been summarized [ 482 ]. As a consequence of its evolutionary plasticity [ 483 ], based on open genome expandability [ 484 , 485 , 486 , 487 ], it is armored with a full arsenal of antibiotic multiresistance [ 3 , 488 , 489 ]. The majority of MDR P. aeruginosa displays a wide repertoire of antibiotic resistance mechanisms, including posttranslational modification of drug targets [ 490 , 491 , 492 ], enzymatic inactivation of antibiotic molecules [ 493 ], encoding genes of carbapenem-resistance preferably those coding for metallo-β-lactamase; overexpressing efflux pumps [ 494 , 495 , 496 ], and showing strong ability to form a biofilm [ 497 , 498 , 499 ].…”
Section: Clonally Evolving Pan-genomic Eskape Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…It can cause diseases in plant and animal species, as well as in humans [ 481 ], which has recently been summarized [ 482 ]. As a consequence of its evolutionary plasticity [ 483 ], based on open genome expandability [ 484 , 485 , 486 , 487 ], it is armored with a full arsenal of antibiotic multiresistance [ 3 , 488 , 489 ]. The majority of MDR P. aeruginosa displays a wide repertoire of antibiotic resistance mechanisms, including posttranslational modification of drug targets [ 490 , 491 , 492 ], enzymatic inactivation of antibiotic molecules [ 493 ], encoding genes of carbapenem-resistance preferably those coding for metallo-β-lactamase; overexpressing efflux pumps [ 494 , 495 , 496 ], and showing strong ability to form a biofilm [ 497 , 498 , 499 ].…”
Section: Clonally Evolving Pan-genomic Eskape Pathogensmentioning
confidence: 99%
“…The most recent overviews [ 487 , 489 ] provides “an ocular perspective” of the different mechanisms of antibiotic resistance in P. aeruginosa . Most strains are intrinsically resistant to third-generation cephalosporins due to chromosomal-encoded C beta-lactamase and AmpC [ 488 , 501 ].…”
Section: Clonally Evolving Pan-genomic Eskape Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, diverse species of Pseudomonas have been isolated from freshwaters (Drucker and Panasyuk, 2006; Morris et al, 2008; Pietsch et al, 2017), including the Great Lakes Erie, Ontario and Superior (Bennett, 1969; Chatterjee et al, 2017). Furthermore, bacteriophage (phage) infectious of Pseudomonas species have been routinely found within Lake Michigan nearshore waters (Malki et al, 2015b; Watkins et al, 2018), thus suggesting the presence of the bacterial host. This motivated the study presented here in which Pseudomonas species found within Chicago’s nearshore waters of Lake Michigan were sequenced and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the approach taken, manual curation and inspection is often a critical step in the process. Several complete viral genomes have been mined from metagenomic data through inspection of sequences based upon their size, coverage, circularity, or sequence homology to annotated viral genes or genes of interest (e.g., Inskeep et al 2013;Labonté & Suttle 2013;Dutilh et al 2014;Smits et al 2014Smits et al , 2015Bellas et al 2015;Rosario et al 2015;Zhang et al 2015;Paez-Espino et al 2016;Voorhies et al 2016;Coutinho et al 2017;Ghai et al 2017;Watkins et al 2018). These efforts have uncovered novel viral species, furthering our understanding of genetic diversity in nature.…”
Section: Introductionmentioning
confidence: 99%